Causas que generan la falta de uniformidad en la aplicación de la agravante cualificada de la reincidencia - Malaver Cruz, Juvissa Gabriela (2019)
ABSTRACT The problem that was investigated was oriented to see the causes that generate the lack of uniformity in the application of the qualified aggravation of recidivism. The general objective was to identify the causes for which the Criminal Courts of the Superior Court of Justice of the Freedom before a factual assumption as the one of the recidivism impose different penalties; likewise, it was justified because an approach to a legislative or jurisprudential scheme was necessary to guide the magistrate when establishing when we are faced with the alleged fact of recidivism, which will contribute to interpreting and duly applying the current law, providing certainty and legal security, in such a way that citizens and users of the administration of justice can foresee and predict that, faced with a certain factual or regulatory situation, the Courts will resolve in a certain sense and under certain parameters previously established, on the other The conclusion was reached that the causes of the lack of uniformity in the application of the qualified aggravation of recidivism are the imprecise legal regulation of the recidivism contemplated in article 46-B of the Penal Code and the lack of development of jurisprudential doctrine after the regulatory reform introduced p or Law No. 30076. For this purpose, all cases in which sentences on recidivism were issued during the period 2014-2017 in the Superior Court of Justice of La Libertad and a survey applied to criminal prosecutors of the Public Prosecutor's Office of the fiscal district of La Libertad were considered as universal population. During the year 2017, a study sample consisting of eight sentences issued on recidivism was extracted by the Criminal Courts and Criminal Chambers of the Superior Court of Justice of La Libertad during the period 2014-2017 and a survey applied to thirty Criminal Prosecutors from The Second and Third Corporate Criminal Provincial Prosecutor's Office of Trujillo in 2017 using non-random sampling, in order to obtain information from the study sample, the following techniques were used: observation, samples, bibliographic records, survey related to the object of study. In the study of information, the following methods were used: scientific, deductive, inductive, analysis, synthesis, dogmatic, hermeneutical. The methodological development was the following: the information of the study sample was given, then it had to go to the Superior Court of Justice of the Freedom for the collection of records of the period 2014-2017, also the prosecutors of the Ministry were interviewed Public of the fiscal district of La Libertad